Effects of Chemical Fertilizers and Pesticides in Agricultural Environment: Impacts of Chemical Fertilizers and Pesticides on Agricultural Environment, Human Health, and Economic Development in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Marketable agricultural surplus is the most significant element that affects a country's economic development in emerging countries like India. As the population grew, so did the need for agricultural commodities, and thus the Green Revolution was born. Developmental countries like India benefited from the Green Revolution, which used high-yielding seed types, modified farming equipment, and significantly increased chemical fertilizer use to produce more food and other agricultural goods. There is no way around the use of chemical fertilizers and pesticides if we are to feed the expanding population without them. The use of such agricultural technologies has allowed food grains to grow and remain viable, but they have had significant negative consequences for both the environment and human health. The impacts of chemical fertilizers and pesticides on human health and the environment are sketched out in this article. Agriculture and metal businesses, together with poor waste management, fertilizers, and pesticides, are polluting our rivers and soils. Pesticides and heavy metals have also been implicated in a wide spectrum of human ailments. In recent years, pesticide-related concerns have been widely have drawn a lot of attention from concerned groups in India.